Analysis of the Influence of Digital Marketing Strategies in Increasing the Accessibility and Attractiveness of Online Education Programmes: A Business and Information Technology Perspective - Widiastuti Furbani; Rino Subekti; Alfan Bachtiar; Rr. Aryanti Kristantini; Bahtiar Efendi (Jurnal Minfo Polgan, 2024)
The digital age has significantly changed the education paradigm. Online education is becoming increasingly popular as an effective and flexible alternative for individuals who want to improve their skills without being bound by geographical and time constraints. However, the success of online education relies heavily on effective digital marketing strategies to increase its accessibility and appeal. The main objective of this study is to analyse the impact and effectiveness of digital marketing strategies in increasing the accessibility and attractiveness of online education programs, focusing on business and information technology perspectives. The research method used in this study is a literature review with a qualitative approach and descriptive analysis. In this context, the literature review will be conducted with a focus on collecting, reviewing and analysing relevant literature from 1981 to 2024. The study results show that digital marketing strategies have a very important role in increasing the accessibility and attractiveness of online education programmes. In particular, the integration between business aspects and information technology is the key to success in optimising marketing performance and achieving business goals of online education institutions.